Mapping Urban Green Space Fragmentation using Drone Technology in Banjarbaru City - Rizali, Akhmad; Abbas, Saipul; Marsuni, Yusriadi; Sari, Yulia Padma; Farah, Nurin Nisa; Noorkomalasari, Noorkomalasari; Badaruddin, Badaruddin (Jurnal Biologi Tropis, 2025)
The rapid urban growth in Banjarbaru City has significantly impacted the quality and quantity of green open spaces. Fragmentation of green spaces poses a major challenge in maintaining the city's ecological balance, particularly amidst high urbanization rates. This study aims to analyze the distribution and fragmentation level of green spaces across five sub-districts in Banjarbaru City using drone technology and spatial approaches. Data were collected through high-resolution aerial mapping and spatially analyzed to identify fragmentation patterns and compare them with the 2024-2043 Spatial Planning (RTRW) of Banjarbaru City. The results show that the highest fragmentation occurs in the Landasan Ulin and South Banjarbaru sub-districts, characterized by small patches and low core vegetation areas. Meanwhile, North Banjarbaru, Cempaka, and Liang Anggang sub-districts still retain extensive and connected green spaces. A comparison with the RTRW reveals a deviation between the planned and actual conditions, particularly in areas designated to be preserved as green open spaces.